23 Mobile Things: self-directed and effective professional learning. Issue 8 (10th November 2014) - Stephens, Michael
Abstract : Purpose: – The purpose of this paper is to examine the "Mobile 23 Things" survey results from the program offered by Guldborgsund-bibliotekerne (a public library in Denmark) and present the findings as support for professional development (PD) models to increase library staff familiarity with emerging technologies. Design/methodology/approach: – Using an integrated, exploratory approach, a web-based survey tool, developed for a previous Learning 2.0 study, was adapted for this study, with survey questions translated English – Danish, and responses Danish – English. The data gathered from both pre- and post-program surveys are presented and analyzed. Findings: – The research results identify that 23 Mobile Things increases familiarity with movable technologies, promotes inclusive learning, and can be an effective model for delivering PD. Originality/value: – This paper reports on the first research study to evaluate the 23 Mobile Things model and provides evidence that this model of library staff PD can be an overall beneficial experience that increases staff knowledge and expertise related to mobile devices and applications.